STRATEGIA DE DEZVOLTARE A BIBLIOTECILOR UNIVERSITARE DIN REPUBLICA MOLDOVA SUB SEMNUL ORIENTĂRII DE MARKETING - REPANOVICI, Prof. univ. dr. irig., Universitatea „Transilvania", Braşov, Angela (BIBLIOPOLIS, 2020)
The research Marketing Orientation as a Strategy for Developing University Libraries in the Republic of Moldova is part of current developments in the area oflibrarianship. The author evaluates the work and highlights particular significance for higher education, the university library role in knowledge development, marketing and enforcement problem library administration's priority in improving the conditions of today's library; emphasizes the relevance of the topic by exemplifying each chapter of the book; it underlines the practical value of the work, offers recommendations that streamline the National System of Libraries.